Key storage management scheme based on keyed hash tree with state - Xiangyu WANG; Jianfeng MA; Yinbin MIAO; Kai ZHANG; Qiying WU (Tongxin xuebao)
To solve the problem of massive keys storage caused by multi-source data encryption in ciphertext retrieval system,a key storage scheme based on keyed hash tree with state was proposed.The scheme computes encryption key according to the root key and key derivation tree,and just needs to store the root key and the tree structure,which greatly reduces the key storage costs.In addition,the scheme manages key revocation according to the revocation state value,thereby solving the problem of key revocation and structure update.Strict security analysis shows that the partial data key disclosure does not leak the data confidentiality of remaining data,and the performance analysis using real-world dataset shows that the proposed key storage management scheme is acceptable in ciphertext retrieval system.